Reinforcing Ninth Graders’ Oral Production through Multiliteracies Approach (2020)
ABSTRACT: This action research project was meant for implementing the Multiliteracies Approach in order to reinforce ninth-grade students’ oral production in a public institution in El Carmen de Viboral. This research involved the participation of thirty-seven ninth grade students. The data collection methods used in this study were teacher’s journal, audio-recordings, students’ products and a focus group interview. After the data analysis, results showed that students reinforced their oral production performance by means of the activities implemented from the four components of the Multiliteracies Approach: situated practice, overt instruction, critical framing, and transformed practice.